The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.jafc.0c01367
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Glutathione S-Transferase Genes in Field λ-Cyhalothrin-Resistant Population of Cydia pomonella: Reference Gene Selection and Expression Analysis

Abstract: Analysis of the glutathione S-transferase (GST) gene expression in an insecticide-resistant strain of Cydia pomonella using real-time quantitative polymerase chain reaction is a key step toward more mechanism studies that require suitable reference genes with stable expression. Here, nine commonly used reference genes were selected, and their expression stabilities were analyzed. Results showed that EF-1α was the most stable reference gene in all of the experimental sets. The combinations of EF-1α and 18S, EF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 56 publications
(145 reference statements)
1
53
1
Order By: Relevance
“…More convincing results were obtained when two genes were used for expression normalization ( Figures 5A,B ). Our results corroborate the current notion of using two or three genes for target gene expression normalization to enhance accuracy (Arya et al, 2017 ; Li et al, 2018c ; Wei et al, 2020 ; Bai et al, 2021 ; Fu and Meyer-Rochow, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…More convincing results were obtained when two genes were used for expression normalization ( Figures 5A,B ). Our results corroborate the current notion of using two or three genes for target gene expression normalization to enhance accuracy (Arya et al, 2017 ; Li et al, 2018c ; Wei et al, 2020 ; Bai et al, 2021 ; Fu and Meyer-Rochow, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…It is worth mentioning that the expression change was more extensive at 37°C for Hsp70 when normalized with NADH , the least stable gene. Recently, elimination of such erroneous findings was achieved by normalization of gene expression with combinations of stable reference genes in different experimental conditions in Helicoverpa armigera (Zhang et al, 2015 ), Aphis gossypii (Ma et al, 2016 ), and Cydia pomonella (Wei et al, 2020 ). Additionally, with the selected single reference genes, such as β -Tubulin (most stable) and RPL17 (least stable), we performed RT-qPCR to study Kr-h1 expression patterns in several developmental stages of ISx ( Figure 5C ).…”
Section: Discussionmentioning
confidence: 99%
“…11 However, the recent development of moderate levels of resistance to λ-cyhalothrin by C. pomonella has been reported in field populations in northeast China. 13 Previous studies have revealed high levels of enzymatic detoxification, mainly due to cytochrome P450, glutathione S-transferases (GST), and esterases (EST), were the primary resistance mechanism in field populations of C. pomonella. 14 GSTs (EC 2.5.1.18) are a diverse family of multifunctional enzymes in the phase II metabolism of xenobiotic substrates that are widely distributed in aerobic organisms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…24 Recombinant CpGSTd1, CpGSTd3, and CpGSTe3 enzymes expressed in Escherichia coli have been shown to indirectly deplete λ-cyhalothrin, 11,15,24 and CpGSTe3 was overexpressed in field-collected λ-cyhalothrin-resistant strains of C. pomonella from northeast China. 13 However, the roles of other GST genes in insecticide metabolisms and resistance remain unclear. increase in nymph mortalities after carbaryl treatment, suggesting that LmGSTs3 may be involved in carbaryl detoxification in Locusta migratoria manilensis (Meyen) (Orthoptera: Acrididae).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The EF1α, encoding a protein associated with translation elongation, is the most abundant protein in the cell and highly conserved in different species (Yin et al, 2020). Several research works have been reported that EF1α is the most stable reference gene in different group of insect species such as Lymantria dispar (Lepidoptera: Lymantriidae) (Yin et al, 2020), Cydia pommnella (Lepidoptera: Tortricidae) (Wei et al, 2020), Aphis gossypii (Hemiptera: Aphididae) (Ma et al, 2016), Locusta migratoria manilensis (Orthoptera: Acrididae) (Yang et al, 2014), and H. convergens (Pan et al, 2015). The ICG website 2 counts the top 10 reported internal reference genes, among which, EF1α is in the first rank (Sang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%